National Law University Library Consortium:Better Late than Never - Rabari, Lagdhir S. (Journal of Information and Knowledge, 2016)
The purpose of this study is to present a model national law library consortium for national law university libraries in India. This study sought the opinion of librarians of 17 national law universities and 8 law publishers. A total of 15 law libraries and 4 law publishers responded. The findings show that except one library, all national law university libraries and law publishers are in favour of a national law university library consortium. Most suggested compulsory participation by all National Law University (NLU) libraries, centralized funding and Common Law Admission Test (CLAT) management model for the proposed National law library consortium.